TNFα-dependent anhedonia and upregulation of hippocampal serotonin transporter activity in a mouse model of collagen-induced arthritis. (15th July 2018) - Brown, Eric; Mc Veigh, Conor J.; Santos, Leilani; Gogarty, Martina; Müller, Heidi Kaastrup; Elfving, Betina; Brayden, David J.; Haase, Jana
Abstract: The serotonin transporter (SERT) facilitates high affinity reuptake of 5-HT from the extracellular fluid and dysregulation of transporter function has been implicated in a range of mood disorders including depression. Recent studies have linked immune system activation to depression as well as to altered serotonin transporter activity. Advancing previous studies, which have mainly focussed on acute effects of immune system activation, in this study we used collagen-induced arthritis (CIA) in mice as a model of chronic inflammatory disease, to investigate the effect of prolonged inflammation on brain SERT function and behaviour. We found that 5–6 weeks after immunisation, CIA mice display anhedonia, a core depression-like behaviour. Behavioural symptoms are temporally correlated with a region-specific upregulation of SERT activity in the hippocampus, which occurs at a post-translational level and is independent of SERT trafficking. Kinetic analysis of 5-HT uptake revealed that the elevation of transporter activity is due to an increase in 5-HT transport capacity (Vmax ) with no change in apparent Km values, suggesting that different regulatory mechanisms govern SERT modulation under chronic versus acute inflammatory conditions. Protein expression of tumour necrosis factor receptor 1 (TNFR1) was specifically upregulated in the hippocampus of CIA mice, indicating altered TNFα signalling. Anti-TNFα treatment using etanercept not only diminished joint inflammation, but also prevented the development of anhedonia and the upregulation of SERT activity in the hippocampus, suggesting a key role for TNFα signalling in brain function regulation in this disease model. Our study provides novel insight into molecular mechanisms underlying mood symptoms in chronic inflammatory diseases, with particular relevance to rheumatoid arthritis. Highlights: Collagen-induced arthritis causes symptoms of anhedonia in mice. Serotonin transporter activity is upregulated in the hippocampus of CIA mice. Anti-TNFα treatment abolishes anhedonia and normalises SERT activity. This study provides novel insight into mechanisms underlying inflammation induced depression.